Window dressing: possibilities and limitations of incremental changes in solitary confinement - Dallas Augustine; Melissa Barragan; Kelsie Chesnut; Natalie A. Pifer; Keramet Reiter; Justin D. Strong (BMC, 2021)
Abstract Background In light of mounting evidence of the physical and psychological harms associated with solitary confinement, many correctional systems, state legislators, courts, and even international human rights bodies are increasingly recommending and implementing reforms to mitigate the harms of solitary confinement, if not abolish the practice entirely. In this piece, we examine three specific infrastructural changes to solitary confinement conditions and practices implemented in Washington state prisons with such harm minimization goals in mind: (1) building so-called "nature imagery rooms" to play videos of outdoor spaces, (2) eliminating punishments for self-harm, and (3) conducting daily cell-front wellness checks. Results Drawing on 183 in-depth qualitative interviews with both staff working in and people imprisoned in solitary confinement units conducted in Washington state restrictive housing units in 2017, we find that these three reforms not only resulted in limited successes but also generated new conflicts. Institutional logics such as deprivation, risk-management, and responsibilization ultimately impeded even the most modest attempts to mitigate the inherently harsh practice of solitary confinement. The limits of these reforms are due in part to individual choices made by people imprisoned in solitary confinement and staff working in these units, as well as the larger cultural norms that shape life in restrictive housing units. Conclusions Incrementalist reforms aimed at softening the environment of solitary confinement may actually serve to increase the strain and stress experienced by people confined to and working within them. Even the most well-intentioned reforms, like those attempted by the Washington DOC, should be scrutinized in order to determine if they are producing the desired outcomes, or instead, reproducing a different, but nonetheless damaging set of harms to people imprisoned in solitary confinement. Further, even well-intentioned reforms are often stymied by the underlying institutional logics of restrictive housing spaces.